Book Review: Mind Over Money (Journal of Financial Therapy, 2019)
Mind Over Money: The Psychology of Money and How to Use It Better, by Claudia Hammond, is an engaging synopsis of multiple research studies from research literature around the world centered on the psychology of money.
Keywords: financial therapy